Analisis Keadilan Upah dan Kesejahteraan Pekerja Rumah Makan Saung Sabdo dalam Perspektif Maqashid Syariah - Akhmad Nurcholis; Fuad YanuarAkhmadRifai; Qurotul Aini (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study aims to analyze wage justice and worker welfare at Saung Sabdo Restaurant from the perspective of Maqashid Sharia. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving the 1 operational manager and workers consisting of 2 cooks, 2 waiters, and 1 cashiers. The findings indicate that the wage system has generally implemented the principles of justice through timely salary payments, opportunities for worship, and harmonious working relationships. Workers’ income was considered sufficient to support daily needs and family necessities. However, worker welfare has not been fully optimal because some workers still face difficulties in meeting long-term economic needs. This study found that wage justice in the perspective of maqashid sharia is not only related to the amount of income, but also includes the protection of spiritual, social, psychological, and overall worker welfare aspects.